In an Era of Terror Threats : Negotiating the Governance of a (Trans)Local Islamic Heritage in the Islamic Republic of Mauritania - Frede, Britta (Claiming and Making Muslim Worlds, 2021)
This chapter scrutinises the negotiation of various actors about the governance of the Mauritanian Islamic heritage. In the context of hopes for democratisation and the war on terror, social frictions are fuelled and lead to a quite confrontational mode of negotiating identity and citizenship. The traditional Islamic educational institution, the maḥḍara, plays a crucial role within these debates. Being perceived as an institution for (re)producing local tradition, the maḥḍara and its visions become the focus of conflict, praised by politicians and the ʿulamāʾ (Islamic scholars) as a driver of social peace, feared by security experts as a breeding ground for terrorism, and finally, wished to be reformed by human right activists. The war on terror goes hand in hand with the threat of terror, producing more rumours than facts and spreading feelings of insecurity that foster violent action.